Between family conflict and school violence - Jacinto Pazo, Pedro (2020)
The manifest forms of verbal or psychological aggression are analyzed, in direct conjunction with physical aggression, which are observed constantly, in the familiar areas of the popular sectors and, which are reproduced in school. In fact, the students admit physical aggression in the home, with figures close to fifty percent in the districts investigated, including with it, the verbal aggression from a majority percentage sense. Of course, what schoolchildren observe is a very violent and aggressive home in its different forms, which a large part of the students finds it impossible to deny. It is manifested, the violence from the parents, but also with more rawness the confrontation between the brothers. Not far from all this, neighborhood or neighborhood violence, which also projects alarming figures and that students perceive daily. It is not a linearity, thinking about explaining the family conflict and its effects on school violence, but warning, the high figures that involve physical aggression in school spaces.